Impact of Hadang and Bentengan Game on Students’ Physical Fitness Levels - Handayani, Widya; Lanos, Muhsana El Cintami; Lestari, Hikmah (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to determine the effectiveness of blocking and fortification games on the physical fitness level of elementary school students. The research method used was experimental using a two-group pretest-posttest design. The sampling technique used purposive sampling and the sample consisted of 54 students. Data collection techniques are 1) documents taken from the results of learning notes during the treatment delivery process, and 2) physical fitness tests is to know physical fitness level. The data analysis technique uses the t-test, but the data analysed must have a normal distribution so that the level of normality and homogeneity of the data is first tested. The t-test results for the Hadang and Bentengan games showed statistically significant increases in physical fitness (e.g., t = 29.105 for Hadang, t = 21.236 for Bentengan, both p 0.05)., so it can be concluded that there was an increase in physical fitness through the Bentengan game. Students' physical fitness levels experienced a significant increase in sprints, pull-ups, sit-ups, vertical jumps and short-distance running activities. The results of this research also have implications for the development of various types of traditional games for other physical fitness learning activities or other health, sports and physical fitness learning activities. Teachers can design types of games as teaching techniques and can be adjusted to the age needs of students such as for elementary or junior high school levels.